Reactive power imbalance method for islanding detection in micro-grid operation - Shamshiri, Meysam; Sapar, Ahmad Farid; Chin, Kim Gan; Tengga Daram, Revinnath; Ab Ghani, Mohd Ruddin (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2014)
Micro-grids usage among consumers has become a new attraction due their several of advantage. Its major function is to ensure the stable operation during the fault and a variety of utility grid disruption. Since the utilization of micro-grid became common, the correct application and operation of micro-grid is importance and significant. One of the main challenges in micro-grids operation is islanding detection methods. There are several methods that are handles the islanding detection that each one have advantage and some disadvantage. This paper presents and investigates the Reactive Power imbalance Method for islanding detection. The passive algorithm implements in this paper due to the low cost operation, however it got the higher non-detection zone (NDZ) and slower response time compare some active methods. The micro-grid simulation is modeled in Matlab/Simulink program and the results of the monitoring are discussed as well. As the result, the performance of the Reactive Power Imbalance method for the islanding detection state is compared with the simulation model without control algorithm. Finally, the micro-grid model capability with control algorithm is shown in order to meet the load demand.